Progress in Studies of the Precipitation Diurnal Variation over Contiguous China - 宇如聪 李建 陈昊明 原韦华 (Acta meteorologica Sinica, 2014)
This paper summarizes the recent progress in studies of the diurnal variation of precipitation over con- tiguous China. The main results are as follows. （1） The rainfall diurnal variation over contiguous China presents distinct regional features. In summer, precipitation peaks in the late afternoon over the south- ern inland China and northeastern China, while it peaks around midnight over southwestern China. In the upper and middle reaches of Yangtze River valley, precipitation occurs mostly in the early morning. Summer precipitation over the central eastern China （most regions of the Tibetan Plateau） has two diurnal peaks, i.e., one in the early morning （midnight） and the other in the late afternoon. （2） The rainfall diurnal variation experiences obvious seasonal and sub-seasonal evolutions. In cold seasons, the regional contrast of rainfall diurnal peaks decreases, with an early morning maximum over most of the southern China. Over the central eastern China, diurnal monsoon rainfall shows sub-seasonal variations with the movement of summer monsoon systems. The rainfall peak mainly occurs in the early morning （late afternoon） during the active （break） monsoon period. （3） Cloud properties and occurrence time of rainfall diurnal peaks are different for long- and short-duration rainfall events. Long-duration rainfall events are dominated by strat- iform precipitation, with the maximum surface rain rate and the highest profile occurring in the late night to early morning, while short-duration rainfall events are more related to convective precipitation, with the maximum surface rain rate and the highest profile occurring between the late afternoon and early night. （4） The rainfall diurnal variation is influenced by multi-scale mountain-valley and land-sea breezes as well as large-scale atmospheric circulation, and involves complicated formation and evolution of cloud and rainfall systems. The diurnal cycle of winds in the lower troposphere also contributes to the regional differences in the rainfall diurnal variation. （5） Evaluation of the model performance shows that the present numerical models are weak in simulating the rainfall diurnal variation over contiguous China. The simulations are not significantly improved by increasing the model horizontal resolution alone. The key is to reduce the uncertainty in physical parameterizations related to the rainfall processes.